First graders’ metalinguistic awareness of the societal prestige of the standard variety - Fehér, Krisztina (Taikomoji kalbotyra, 2024)
This paper discusses first graders’ linguistic biases in a Hungarian town where both the standard and the local varieties are used. Tests and interviews were conducted to determine whether the children who preferred the standard variety to the local dialect were able to verbalize their biases. In a preceding study conducted in the same town, kindergarteners of both genders preferred the standard variety but could not justify their linguistic choices. The current work showed that children became more judgmental and more aware of their biases in the first year of school. First graders commented on their preferences and followed the adult stereotype when describing the typical local speaker as “older, rural, male”. However, there was no evidence of gendered socialization in the children’s linguistic preferences. The qualitative change in the first graders’ metalinguistic awareness of the prestige of varieties highlights the impact of school on sociolinguistic acquisition.